Market Reaction to the Issuance of Capital Instruments by Brazilian Banks - André Ricardo Moncaio Zanon; José Alves Dantas (BBR: Brazilian Business Review)
Banks are allowed to employ debt instruments in order to meet the minimum requirements of capital, as long as they comply with the subordination agreements as determined by the Basel Accords. This paper takes account of the effective powers of these instruments, viewed from the standpoint of the investors, and seeks to assess their impact on the return on investments in the shares of the issuing banks within Brazil’s capital markets. The article is, to a large extent, based on the research findings of Ammann et al (2017). The results of the empirical tests - which were conducted by means of event studies that involved issuing 30 instruments during the period 12/2008 - 09/2017 - suggest that the issuances or announcements of these instruments had an adverse effect on the stock market value of the issuing banks. In addition, evidence was obtained that the market is unable to forecast the effects of these instruments before they take place. This paper seeks to contribute to the current literature on prudential regulations for banking and it hopes to assist banks in making decisions about capitalization.